2015
DOI: 10.1242/jcs.179424
|View full text |Cite
|
Sign up to set email alerts
|

A local VE-cadherin and Trio-based signaling complex stabilizes endothelial junctions through Rac1

Abstract: There was an error published in J. Cell Sci. 128, 3041-3054.The name of Dr Fukuhara was incomplete in the acknowledgements section. The complete acknowledgements section should read as below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…This local Rac1 activity co-localized with a-catenin, one of the VE-cadherin complex members, and likely stabilized the nascent contacts by promoting the formation of cortical actin bundles. 22 In line with this finding, a rapid increase in Rac1 activity upon VE-cadherin homotypic adhesion was detected biochemically, which was induced using beads coated with the VE-cadherin ectodomain. Thus, as was shown for E-, M-and N-cadherin, [64][65][66][67] we showed that VEcadherin can signal in an outside-in fashion to activate Rac1, providing a bidirectional feedback mechanism.…”
Section: Endothelial Adherens Junction Control By Rho Gtpasessupporting
confidence: 67%
See 4 more Smart Citations
“…This local Rac1 activity co-localized with a-catenin, one of the VE-cadherin complex members, and likely stabilized the nascent contacts by promoting the formation of cortical actin bundles. 22 In line with this finding, a rapid increase in Rac1 activity upon VE-cadherin homotypic adhesion was detected biochemically, which was induced using beads coated with the VE-cadherin ectodomain. Thus, as was shown for E-, M-and N-cadherin, [64][65][66][67] we showed that VEcadherin can signal in an outside-in fashion to activate Rac1, providing a bidirectional feedback mechanism.…”
Section: Endothelial Adherens Junction Control By Rho Gtpasessupporting
confidence: 67%
“…We recently showed that binding of the GEF Trio to VE-cadherin is a crucial event to stabilize endothelial cell-cell junctions. 22 Trio displays 2 GEF domains of distinct specificity, enabling activation of multiple Rho GTPases: Rac1, RhoG and RhoA. 23,24 Our findings suggest that by activating Rac1 at junctions, Trio promotes the formation of cortical actin bundles adjacent to the junction, which is concomitant with the stabilization of cell-cell junctions and supports endothelial barrier function.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations